The genetic and psychological underpinnings of generalized social trust. Issue 1 (2nd January 2019) - Weinschenk, Aaron C.; Dawes, Christopher T.
ABSTRACT: In this paper, we investigate the genetic and psychological underpinnings of generalized social trust, an orientation that refers to one's expectations about the trustworthiness of strangers. We make a number of contributions to the literature. First, using a new dataset containing information on a large sample of German twin pairs ( N = 1980 pairs), we replicate previous studies on the heritability of social trust. Our analysis supports previous research showing modest heritability estimates for social trust. Second, we examine whether seven different psychological traits (openness, conscientiousness, extraversion, agreeableness, neuroticism, self-efficacy, and cognitive ability) are related to social trust, a number of which we find are correlated with trust in theoretically expected ways. Lastly, we estimate the extent to which genetic factors account for the correlation between psychological traits and social trust. We find evidence that genetic factors account for a large amount of the correlation between social trust and two psychological traits-agreeableness and neuroticism. In addition, we find that the correlation between cognitive ability and social trust is primarily due to common environment. Our results provide important insights on the underpinnings of social trust.